Predictive Effect of Serial Serum Alanine Aminotransferase Levels on Spontaneous HBeAg Seroconversion in Chronic Genotype B and C HBV–Infected Children - Wu, Jia-Feng (2012)
OBJECTIVE: The present study aimed to investigate the association between serial serum alanine aminotransferase (ALT) and spontaneous hepatitis B e antigen (HBeAg) seroconversion age in chronic hepatitis B virus (HBV)–infected children. PATIENTS AND METHODS: One hundred four HBeAg-positive chronic genotype B or C HBV–infected patients were included in this long-term prospective cohort study (mean initial age 7.20 years). Serial serum ALT levels and HBV serology markers were measured every 6 to 12 months. The 104 subjects made a total of 2525 visits during the study period, and the majority (93.6%) of visits were within a 1-year interval apart from previous visits. Cox proportional hazards model with time-dependent covariates was used in the survival analysis of HBeAg in these subjects. RESULTS: During the chronic course of HBV infection, the median remaining times to spontaneous HBeAg seroconversion were 8.35, 5.14, 4.25, 3.95, and 2.80 years after the ALT levels crossed 20, 30, 40, 60, and 150 IU/L, respectively. The incidence rate of spontaneous HBeAg seroconversion within 6 months when a subject entered the phase of ALT between 60 and 150 IU/L was 5.57 times that of the phase with ALT <60 IU/L. The incidence rate of HBeAg seroconversion once ALT levels were above 150 IU/L was 9.87 times that of the phase of ALT <60 IU/L. CONCLUSIONS: The ALT levels above 30 IU/L served as a cutoff of the inflammatory phase in chronic genotype B and C HBV–infected patients. Serial ALT levels in chronic HBV–infected subjects offer a predicted effect on the occurrence of spontaneous HBeAg seroconversion.